Chemical and Antibacterial Polymorphism of Juniperus oxycedrus ssp. oxycedrus and Juniperus oxycedrus ssp. macrocarpa (Cupressaceae) Leaf Essential Oils from Tunisia - Hnène Medini; Bruno Manongiu; Neffati Aicha; Leila Chekir-Ghedira; Fethia Harzalla-Skhiri; Med Larbi Khouja (Journal of Chemistry)
Essential oils from Juniperus oxycedrus L. have been used since antiquity for fragrance, flavoring, medicinal, antimicrobial, insecticidal, and cosmetic purposes. Several works studied the chemical composition of the essential oils of Juniperus oxycedrus leaves. The aim of this study is to investigate the chemotaxonomic relationships and antibacterial activity of two Tunisian subspecies: Juniperus oxycedrus ssp. oxycedrus (L. K.) Deb. and Juniperus oxycedrus ssp. macrocarpa (S. & m.) Ball. In addition, and for the first time, we reported the antibacterial activities of Tunisian J. oxycedrus ssp. macrocarpa and J. oxycedrus ssp. oxycedrus against four bacteria. Essential oils obtained by hydrodistillation were analysed by GC and GC/MS. Fifty-five constituents were identified. Thirty four major compounds were retained for the study of the chemical variability, and α-pinene, sylvestrene, p-cymene, and 13-epi-manoyl oxide were the main ones. The chemical principal components analysis (PCA) identified three chemotypes. The study of the antibacterial activity showed that Escherichia coli was found to be extremely resistant (zone diameter 0 mm) to all the oils tested, while Staphylococcus aureus was the most sensitive strain (zone diameter 13.5 mm and MIC ranged from 600 to 650 μg/mL).